Investigation of mechanical properties of twin gold crystal nanowires under uniaxial load by molecular dynamics method - 张国伟 杨在林 罗刚 (Chinese physics B, 2016)
Twin gold crystal nanowires, whose loading direction is parallel to the twin boundary orientation, are simulated.We calculate the nanowires under tensile or compressive loads, different length nanowires, and different twin boundary nanowires respectively. The Young modulus of nanowires under compressive load is about twice that under tensile load.The compressive properties of twin gold nanowires are superior to their tensile properties. For different length nanowires,there is a critical value of length with respect to the mechanical properties. When the length of nanowire is greater than the critical value, its mechanical properties are sensitive to length. The twin boundary spacing hardly affects the mechanical properties.